2016
DOI: 10.1248/cpb.c16-00500
|View full text |Cite
|
Sign up to set email alerts
|

Crotofolane-Type Diterpenoids, Crotocascarins L–Q, and a Rearranged Crotofolane-Type Diterpenoid, Neocrotocascarin, from the Stems of <i>Croton cascarilloides</i>

Abstract: From the stems of Croton cascarilloides, further crotofolane-type diterpenoids, named crotocascarins L-Q (1-6), and a rearranged one (7), named neocrotocascarin were isolated. Their structures were elucidated from spectroscopic evidence. Also, the structures of crotocascarin O (4) and neocrotocascarin (7) were determined by X-ray crystallographic analyses. As a result, neocrotocascarin (7) was found to possess a new carbon framework. A plausible mechanism for the formation of neocrotocascarin (7) is also discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 9 publications
3
16
0
Order By: Relevance
“…Twenty-four new crotofolane diterpenoids ( 189 – 198 , 212 – 222 , 225 – 227 ) were isolated from C . caracasanus [ 68 , 69 , 70 , 71 ]. Among them, three new crotofolane diterpenoid alkaloids, cascarinoids A–C ( 225 – 227 ), were firstly found.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Twenty-four new crotofolane diterpenoids ( 189 – 198 , 212 – 222 , 225 – 227 ) were isolated from C . caracasanus [ 68 , 69 , 70 , 71 ]. Among them, three new crotofolane diterpenoid alkaloids, cascarinoids A–C ( 225 – 227 ), were firstly found.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…6) Several studies have reported the isolation of diterpenoids, triterpenoids, and flavonoid from C. cascarilloides, such as 3-acetyl aleuritolic acid, rubiadin-1-methyl ether, and julocrotine, ent-8,9-seco-7α-hydroxy-11β-acetoxykaura-8 (14), 16-dien-9,15-dione, ent-8,9-seco-8,14-epoxy-7α-hydroxy-11βacetoxy-16-kauren-9,15-dione, ent-8,9-seco-7α-hydroxykaura-8 (14),16-dien-9,15-dione, luteolin-7-O-α-L-rhamnoside. 15) Our further extensive study on the leaves and stems of C. cascarilloides revealed the presence of many structurally interesting compounds including megastigmane glycosides, crotonionosides A-G (75-81), crotofolane-type diterpenoids, crotocascarins A-Q (82-98), isocrotofolane glucoside (99), neocrotocascarin (100), and crotocascarin α-γ (101-103) [16][17][18][19][20] (Fig. 5).…”
Section: Phytochemical Analysis Of Croton Cascarilloidesmentioning
confidence: 99%
“…4. 17) From the stems of C. cascarilloides, structurally rare croto- folane-type diterpenoids (82-98) and three new skeletons, i.e., isocrotoforane (99), neocrotocascarin (100), and rearranged nor-crotofolanes α-γ (101-103), were isolated [18][19][20] (Fig. 5).…”
Section: Phytochemical Analysis Of Croton Cascarilloidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemistry of Croton genus shows a high diversity of structures: diterpenes of different skeletons including crotofolanes (Chávez et al, 2013;Kawakami et al, 2015), clerodanes (Pizzolatti et al, 2013;Aldhaher et al, 2017;Qiu et al, 2018), kaurenes (Mora et al, 2011;Mateu et al, 2012;Pereira et al, 2012), labdanes (Bernardino et al, 2017), the more important structures in many species (Xu et al, 2018;Shi et al, 2018). Terpenes (Palmeira Júnior et al, 2006); alkaloids and flavonoids are also common in the genus (de Araújo- Júnior et al, 2004;Suárez et al, 2004;Cerqueira-Coelho et al, 2016).…”
Section: Introductionmentioning
confidence: 99%